Sie sind auf Seite 1von 9

# Econ 325 Section 003/004

By Hiro Kasahara

## Properties of Summation Operator

For a sequence of the values {x1 , x2 , ..., xn }, we write the sum of x1 , x2 , ..., xn−1 , and xn using the
summation operator as
Xn
x1 + x2 + ... + xn = xi . (1)
i=1
Given a constant c,
n
X n
X
cxi = cx1 + cx2 + ... + cxn = c × (x1 + x2 + ... + xn ) = c xi . (2)
i=1 i=1

• For example, consider the case thatPn = 2 with the values of {x1 , x2 } given by xP
1 = 0 and
x2 = 1. Suppose that c = 4. Then, i=1 4 × xi = 4 × 0 + 4 × 1 = 4 × (0 + 1) = 4 2i=1 xi .
2

## • In the special case of x1 = x2 = ... = xn = 1, we have ni=1 cxi = ni=1 c × 1 = c × ni=1 1 =

P P P
c × (1 + 1 + ... + 1) = nc.

Consider another sequence {y1 , y2 , ..., ym } in addition to {x1 , x2 , ..., xn }. Then, we may consider
doubleP
summations over possible values of x’s and y’s. For example, consider the case of n = m = 2.
Then, 2i=1 2j=1 xi yj is equal to x1 y1 + x1 y2 + x2 y1 + x2 y2 because
P

x1 y1 + x1 y2 + x2 y1 + x2 y2
= x1 (y1 + y2 ) + x2 (y1 + y2 ) (by factorization)
2
X
= xi (y1 + y2 ) (by def. of the summation operator by setting c = (y1 + y2 ) in (2) )
i=1
 
2
X 2
X P2
= xi  yj  (because y1 + y2 = j=1 yj )
i=1 j=1
 
2
X X2
P2 P2
=  x i yj  (because xi j=1 yj = xi (y1 + y2 ) = (xi y1 + xi y2 ) = j=1 xi yj )
i=1 j=1
2 X
X 2
= xi yj .
i=1 j=1

• Note thatP 2i=1P 2j=1 xi yj =P 2j=1P 2i=1 xi yj . In general case of {x1 , x2 , ..., xn } and {y1 , y2 , ..., ym },
P P P P
we have ni=1 m j=1 xi yj =
m
j=1
n
i=1 xi yj .

• Note that 2j=1 xi yj = xi 2j=1 yj using (2) because xi is treated as a constant in the sum-
P P
mation operator over j’s. Hence, we can write
2 X
X 2 2
X 2
X 2
X 2
X
xi yj = xi yj = yj xi .
i=1 j=1 i=1 j=1 j=1 i=1

1
In general, we have
n X
X m n
X m
X m
X n
X
xi yj = xi yj = yj xi . (3)
i=1 j=1 i=1 j=1 j=1 i=1

That is, when we have double summations, we can take xi ’s out of the summation over j’s.
Similarly, we can take yj ’s out of the summation over i’s.

## Expectation, Variance, and Covariance

Let X and Y be two discrete random variables. The set of possible values for X is {x1 , . . . , xn };
and the set of possible values for Y is {y1 , . . . , ym }. The joint probability function is given by

pX,Y
ij = P (X = xi , Y = yj ) , i = 1, . . . n; j = 1, . . . , m.

## The marginal probability function of X is

m
pX,Y
X
pX
i = P (X = xi ) = ij , i = 1, . . . n,
j=1

## and the marginal probability function of Y is

n
pX,Y
X
pYj = P (Y = yj ) = ij , j = 1, . . . m.
i=1

1. If c is a constant, then

## Proof: By definition of the expected value of cX,

n
X
E[cX] = (cxi )pX
i (by def. of the expected value)
i=1
= cx1 pX X X X X
1 + cx2 p2 + cx3 p3 + ... + cxn−1 pn−1 + cxn pn (by def. of the summation operator)
=c× (x1 pX
1 + x2 pX
2 + x3 pX
3 + ... + xn−1 pX
n−1 + xn p X
n) (because c is a common factor)
n
!
X
=c× xi p X
i (by def. of the summation operator)
i=1
= c × E[X] (by def. of the expected value of X)
= cE[X].

2.
E[X + Y ] = E[X] + E[Y ]. (5)

2
Proof:
n X
m
(xi + yj )pX,Y
X
E(X + Y ) = ij
i=1 j=1
n X
m
(xi pX,Y + yj pX,Y
X
= ij ij )
i=1 j=1
n X m n X
m
xi pX,Y yj pX,Y
X X
= ij + ij (6)
i=1 j=1 i=1 j=1
 
n m m n
!
X,Y 
pX,Y
X X X X
= xi ·  pij + yj · ij (7)
i=1 j=1 j=1 i=1
Pm
because we can take xi out of j=1 because xi does not depend on j’s
n
X m
X
= xi · pX
i + yj · pYj
i=1 j=1
Pm X,Y Pn X,Y
because pX
i = j=1 pij and pYj = i=1 pij
= E(X) + E(Y )

## X,Y X,Y X,Y Pn Pm X,Y

Equation (6): To understand ni=1 m
P P Pn Pm
j=1 (xi pij +yj pij ) = i=1 j=1 xi pij + i=1 j=1 yj pij ,
consider the case of n = m = 2. Then,
2 X
2
(xi pX,Y + yj pX,Y
X
ij ij )
i=1 j=1

## = (x1 pX,Y X,Y X,Y X,Y X,Y X,Y X,Y X,Y

11 + y1 p11 ) + (x1 p12 + y2 p12 ) + (x2 p21 + y1 p21 ) + (x2 p22 + y2 p22 )
= (x1 pX,Y X,Y X,Y X,Y X,Y X,Y X,Y X,Y
11 + x1 p12 + x2 p21 + x2 p22 ) + (y1 p11 + y2 p12 + y1 p21 + y2 p22 )
2 X
2 2 X
2
xi pX,Y yj pX,Y
X X
= ij + ij .
i=1 j=1 i=1 j=1
Pn Pm X,Y Pn
Equation (7): This is a generalization of (3). To understand i=1 j=1 xi pij = i=1 xi ·
X,Y
( m
P
j=1 pij ), consider the case of n = m = 2. Then,

2 X
2
xi pX,Y = x1 pX,Y X,Y X,Y X,Y
X
ij 11 + x1 p12 + x2 p21 + x2 p22
i=1 j=1

## = x1 (pX,Y X,Y X,Y X,Y

11 + p12 ) + x2 (p21 + p22 )
2
xi (pX,Y + pX,Y
X
= i1 i2 )
i=1
2 2
pX,Y
X X
= xi ( ij ).
i=1 j=1

X,Y
· ( 2i=1 pX,Y
P2 P2 P2 P
Similarly, we may show that i=1 j=1 yj pij = j=1 yj ij ).

## 3. If a and b are constants, then E[a + bX] = a + bE[X].

3
Proof:
n
X
E(a + bX) = (a + bxi )pX
i
i=1
n
X
= (apX X
i + bxi pi )
i=1
Xn n
X
= apX
i + bxi pX
i (8)
i=1 i=1
Xn Xn
=a pX
i +b xi p X
i , (by using (2))
i=1 i=1
Pn X
Pn Pn X
= a · 1 + bE(X), where i=1 pi = i=1 P (X = xi ) = 1 and i=1 xi pi = E(X)
= a + bE(X).
Pn X + bx pX ) =
Pn X
Equation
Pn (8): This is similar to (6). To understand i=1 (ap i i i i=1 api +
X
P 2 X + bx pX ) = (apx + bx pX ) + (apx +
P2 i=1 (ap
i=1 bxi pi , consider the case of n = 2. Then, i P i i 1 1 1 2
bx2 p2 ) = (ap1 + ap2 ) + (bx1 p1 + bx2 p2 ) = i=1 api + 2i=1 bxi pX
X x x X X X
i .

## Cov(X, c) = E[(X − E(X))(c − c)]

= E[(X − E(X)) · 0]
= E[0]
Xn
= 0 × pX
i
i=1
Xn
= 0
i=1
= 0 + 0 + ... + 0
=0

## 5. Cov (X, X) = V ar (X) .

4
Proof: According to the definition of covariance, we can expand Cov(X, X) as follows:

## Cov(X, X) = E[(X − E(X))(X − E(X))]

Xn n
X
= [xi − E(X)][xi − E(X)] · P (X = xi ), where E(X) = xi p X
i
i=1 i=1
Xn
= [xi − E(X)][xi − E(X)] · pX
i
i=1
Xn
= [xi − E(X)]2 · pX
i
i=1
= E[(X − E(X))2 ] (by def. of the expected value)
= V ar(X).

## Cov(X, Y ) = E[(X − E(X))(Y − E(Y ))]

n Xm n m
[xi − E(X)][yj − E(Y )] · pX,Y
X X X
= ij , where E(X) = xi p X
i and E(Y ) = yj pYj
i=1 j=1 i=1 j=1
m X n
[yj − E(Y )][xi − E(X)] · pX,Y
X
= ij
j=1 i=1

## = E[(Y − E(Y ))(X − E(X))] (by def. of the expected value)

= Cov(Y, X). (by def. of the covariance)

## Proof: Using E(a1 + b1 X) = a1 + b1 E(X) and E(a2 + b2 Y ) = a2 + b2 E(Y ), we can expand

Cov (a1 + b1 X, a2 + b2 Y ) as follows:

## Cov(X, Y ) = E[(a1 + b1 X − E(a1 + b1 X))(a2 + b2 Y − E(a2 + b2 Y ))]

= E[(a1 + b1 X − (a1 + b1 E(X)))(a2 + b2 Y − (a2 + b2 E(Y ))]
= E[(a1 − a1 + b1 X − b1 E(X))(a2 − a2 + b2 Y − b2 E(Y )]
= E[(b1 X − b1 E(X))(b2 Y − b2 E(Y )]
= E[b1 (X − E(X)) · b2 (Y − E(Y ))]
= E[b1 b2 (X − E(X))(Y − E(Y ))]
n X m
b1 b2 (xi − E(X))(yj − E(Y )) · pX,Y
X
= ij
i=1 j=1
n X
m
[xi − E(X)][yj − E(Y )] · pX,Y
X
= b1 b2 ij (by using (2))
i=1 j=1

= b1 b2 Cov(X, Y ).

5
8. If X and Y are independent, then Cov (X, Y ) = 0.

## Proof: If X and Y are independent, by definition of stochastic independence, P (X = xi , Y =

yj ) = P (X = xi )P (Y = yj ) = pX Y
i pj for any i = 1, ..., n and j = 1, ..., m. Then, we may
expand Cov (X, Y ) as follows.

## Cov(X, Y ) = E[(X − E(X))(Y − E(Y ))]

Xn Xm
= [xi − E(X)][yj − E(Y )] · P (X = xi , Y = yj )
i=1 j=1
n X
X m
= [xi − E(X)][yj − E(Y )]pX Y
i pj
i=1 j=1

## because X and Y are independent

n X
X m
= {[xi − E(X)]pX Y
i }{[yj − E(Y )]pj }
i=1 j=1
 
n
X Xm 
= [xi − E(X)]pX
i [yj − E(Y )]pYj (9)
 
i=1 j=1
Pm
because we can move [xi − E(X)]pX
i outside of j=1
because [xi − E(X)]pX does not depend on the index j’s
  (i
m n
)
X  X
= [yj − E(Y )]pYj [xi − E(X)]pX i (10)
 
j=1 i=1
nP o
m Y outside of ni=1
P
because we can move j=1 j[y − E(Y )]pj
nP o
m Y
because [y
j=1 j − E(Y )]pj does not depend on the index i’s
( n  
n m m
)
X X X X 
= xi p X
i − E(X)pX i · yj pYj − E(Y )pYj
 
i=1 i=1 j=1 j=1
( n
)  m

X  X 
X Y
= E(X) − E(X)pi · E(Y ) − E(Y )pj
 
i=1 j=1

## by definition of E(X) and E(Y )

( n
)  m

X  X 
= E(X) − E(X) pX
i · E(Y ) − E(Y ) pYj
 
i=1 j=1
Pn Pm
because we can move E(X) and E(Y ) outside of i=1 and j=1 , respectively
= {E(X) − E(X) · 1} · {E(Y ) − E(Y ) · 1}
= 0 · 0 = 0.

Equations (9) and (10): This is similar to equations (3) and (7). Please consider the case of
n = m = 2 and convince yourself that (9) and (10) hold.

## 9. V ar (X + Y ) = V ar (X) + V ar (Y ) + 2Cov (X, Y ).

6
Proof: By the definition of variance,

Then,

## V ar(X + Y ) = E[(X + Y − E(X + Y ))2 ]

= E[((X − E(X)) + (Y − E(Y )))2 ]
= E[(X − E(X))2 + (Y − E(Y ))2 + 2(X − E(X))(Y − E(Y ))]
because for any a and b, (a + b)2 = a2 + b2 + 2ab
= E[(X − E(X))2 ] + E[(Y − E(Y ))2 ] + 2E[(X − E(X))(Y − E(Y ))] (by using (5))
= V ar(X) + V ar(Y ) + 2Cov(X, Y )
by definition of variance and covariance

## Proof: The proof of V ar (X − Y ) = V ar (X) + V ar (Y ) − 2Cov (X, Y ) is similar to the proof

of V ar (X + Y ) = V ar (X) + V ar (Y ) + 2Cov (X, Y ). First, we may show that E(X − Y ) =
E(X) − E(Y ). Then,

## V ar(X − Y ) = E[(X − Y − E(X − Y ))2 ]

= E[((X − E(X)) − (Y − E(Y )))2 ]
= E[(X − E(X))2 + (Y − E(Y ))2 − 2(X − E(X))(Y − E(Y ))]
= E[(X − E(X))2 ] + E[(Y − E(Y ))2 ] − 2E[(X − E(X))(Y − E(Y ))] (by using (5))
= V ar(X) + V ar(Y ) − 2Cov(X, Y )
p p
11. Define W = (X −E(X))/ V ar(X) and Z = (Y −E(Y ))/ V ar(Y ). Show that Cov(W, Z) =
Corr(X, Z).

7
Proof: Expanding Cov(W, Z), we have

## Cov(W, Z) = E[(W − E(W ))(Z − E(Z))]

= E[W Z] (because E[W ] = E[Z] = 0)
( )
X − E(X) Y − E(Y )
=E p ·p
V ar(X) V ar(Y )
by definition of W and Z
( )
1 1
=E p ·p · [X − E(X)]E[Y − E(Y )]
V ar(X) V ar(Y )
1 1
=p ·p · E {[X − E(X)]E[Y − E(Y )]} (by using (2) and (4))
V ar(X) V ar(Y )
because both √ 1 and √ 1 are constant
V ar(X) V ar(Y )
E {[X − E(X)]E[Y − E(Y )]}
= p p
V ar(X) V ar(Y )
Cov(X, Y )
=p p (by definition of covariance)
V ar(X) V ar(Y )
= Corr(X, Y ) (by definition of correlation coefficient)

12. Let {xi : i = 1, . . . , n} and {yi : i = 1, . . . , n} be two sequences. Define the averages
n
1X
x̄ = xi ,
n
i=1
n
1X
ȳ = yi .
n
i=1
Pn
(a) i=1 (xi − x̄) = 0.

Proof:
n
X n
X n
X
(xi − x̄) = xi − x̄
i=1 i=1 i=1
n
X
= xi − nx̄
i=1
because ni=1 x̄ = x̄ + x̄ + ... + x̄ = nx̄
P
Pn
xi
= n i=1 − nx̄
n Pn
xi
because ni=1 xi = nn ni=1 xi = n i=1
P P
n
= nx̄ − nx̄
Pn
xi
because x̄ = i=1
n
= 0.
Pn
− x̄)2 =
Pn
(b) i=1 (xi i=1 xi (xi − x̄).

8
Proof: We use the result of 2.(a) above.
n
X n
X
2
(xi − x̄) = (xi − x̄) (xi − x̄)
i=1 i=1
Xn n
X
= xi (xi − x̄) − x̄ (xi − x̄)
i=1 i=1
Xn Xn
= xi (xi − x̄) − x̄ (xi − x̄)
i=1 i=1
n
X
because x̄ is constant and does not depend on i’s = xi (xi − x̄) − x̄ · 0
i=1
because ni=1 (xi − x̄) = 0. as shown above
P
n
X
= xi (xi − x̄) .
i=1
Pn Pn Pn
(c) i=1 (xi − x̄) (yi − ȳ) = i=1 yi (xi − x̄) = i=1 xi (yi − ȳ).

## Proof: The proof is similar to the proof of 2.(b) above.

n
X n
X n
X
(xi − x̄) (yi − ȳ) = (xi − x̄) yi − (xi − x̄) ȳ
i=1 i=1 i=1
Xn Xn
= (xi − x̄) yi − ȳ (xi − x̄)
i=1 i=1
Xn
= (xi − x̄) yi − ȳ · 0
i=1
Xn
= yi (xi − x̄) .
i=1

Also,
n
X n
X n
X
(xi − x̄) (yi − ȳ) = xi (yi − ȳ) − x̄ (yi − ȳ)
i=1 i=1 i=1
Xn Xn
= xi (yi − ȳ) − x̄ (yi − ȳ)
i=1 i=1
Xn
= xi (yi − ȳ) − x̄ · 0
i=1
Xn
= xi (yi − ȳ) .
i=1